Cryptic diversity in the mayfly Leptohyphodes inanis (Pictet) (Ephemeroptera: Leptohyphidae) across water basins in Southeastern Brazil. Issue 7 (3rd October 2021) - Souto, Paula Malaquias; da Silveira, Luiz Felipe Lima; Takiya, Daniela Maeda; Salles, Frederico Falcão
Abstract : Leptohyphodes inanis (Pictet) is an enigmatic species with a rare trait among leptohyphid males – large and divided compound eyes. In addition, the color of its upper portion is variable across – but not within – populations. However, the geographic variation of this trait and its relation to gene flow across populations remain unknown. Here, we analyzed individuals across Southeastern Brazil (19º to 24ºS and 40º to 48º W) to (i) assess genetic (COI) and eye color variation, and (ii) evaluate if L. inanis is a single species, by combining Bayesian phylogenetic analyses (including two other leptohyphid genera – Tricorythopsis and Tricorythodes ) and species delimitation methods: ABGD and mPTP. To further investigate within-species variation in phenotypic traits, we evaluated quantitative and qualitative morphological traits of 1, 252 individuals. We found that genetic variation in L. inanis is largely unrelated to eye color, and that pairwise genetic divergences in COI mtDNA are remarkably higher (up to 30.7%) than previously found in other mayfly lineages. L. inanis was recovered as monophyletic, although results suggest it includes three to seven cryptic species, each one related to mountain ranges across Southeastern Brazil. Furthermore, we found no genetic variation among individuals of the same drainage basin, suggesting that populations might be largely isolated from one another. Because morphological traits traditionally used in Ephemeroptera taxonomy were ineffective in distinguishing the cryptic species, we propose L. inanis to be a species complex.